Integrated Straw Return with Less Power Puddling Improves Soil Fertility and Rice Yield in China’s Cold Regions - Donghui Liu; Pengfei Li; Wenyu Wu; Shunyao Yu; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (Agronomy, 2024)
The rice production system in China is facing challenges, including declining soil fertility and a stagnant rice yield. This study aimed to test whether integrating the return of straw to fields with less power puddling could simultaneously enhance soil fertility and rice yields. Therefore, field experiments were conducted in Heilongjiang Province, a key rice-growing region in China, from 2017 to 2021, using three different planting methods: control group (CK), straw return (SR) and straw return integrated with less power puddling (SR + LP). The results showed that small soil aggregates (particle diameter < 0.25 mm) and soil bulk density were significantly decreased when straw return was integrated with less power puddling. These changes contributed to the preservation of soil structure. Simultaneously, this approach significantly increased soil ammonium nitrogen content from 9.9 to 10.9 mg kg−1, organic matter content from 35.0 to 36.2 g kg−1, available nitrogen content from 140.5 to 147.0 mg kg−1 and available potassium content from 128.6 to 136.8 mg kg−1 at mature stage on average. Consequently, the post-heading stored assimilates accumulation of rice was increased from 6.12 to 6.43 t ha−1, and the nitrogen, phosphorus and potassium accumulation of rice were increased by 7.85 kg ha−1, 1.13 kg ha−1 and 5.68 kg ha−1, respectively. These changes ultimately resulted in a higher 1000 g weight and filled grain rate, providing the foundation for higher yields (an increase from 9.31 t ha−1 to 9.55 t ha−1). Furthermore, this approach also increased the net income for farmers by USD 14 t ha−1. In summary, this study demonstrates that integrating straw return with less power puddling can enhance soil’s nutrient supply and retention capacity. This enhancement may boost the absorption and transportation of nutrients, ultimately establishing the groundwork for higher yields and economic benefits by enhancing the 1000 g weight and filled grain rate. Future research should delve deeper into its applicability across different ecosystems and investigate the yield-increasing mechanisms.